1984
DOI: 10.1111/j.1834-7819.1984.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐coronal resorption of unerupted molars

Abstract: Abstract— Histological and clinical evidence exists to show that external coronal resorption of unerupted molars does not extend to the pulp chamber. This paper recommends surgical exposure and restoration of these teeth before progression of the resorptive process weakens the coronal tissue to such an extent that a satisfactory restoration is difficult to achieve. Failure to eliminate the defect before eruption may result in microbial contamination, rapid destruction of the underlying dentine, pulpal and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
1
14
0
3
Order By: Relevance
“…In the present study, all the cases of intracoronal resorption were located just beneath the dentinoenamel junction, as reported in previous studies (Grundy et al ., ; Seow et al ., ; Hata et al ., ; Özden and Acikgoz, ; Al‐Batayneh et al, ; Uzun et al ., ). Al‐Batayneh et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all the cases of intracoronal resorption were located just beneath the dentinoenamel junction, as reported in previous studies (Grundy et al ., ; Seow et al ., ; Hata et al ., ; Özden and Acikgoz, ; Al‐Batayneh et al, ; Uzun et al ., ). Al‐Batayneh et al .…”
Section: Discussionmentioning
confidence: 99%
“…2-478 Although the etiology and factors associated with the initiation of resorption remain unknown, resorptive cells originating from the surrounding bone are thought to enter the dentin through a break in the dental follicle and enamel or cementum. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Usually, the occlusal enamel surface is intact (Johnson & Harkness, 1997;Kupietzky, 1999;Seow, 1998;Singer & others, 1991;Wood & Crozier, 1985), with a chalky, grayish, dry, flaky dentin that has a different consistency from caries-induced demineralized dentin (Kunz, 1997;Seow, 1998). Histological examination has shown resorption (Grundy, Pyle & Adkins, 1984;Rankow, Croll & Miller, 1986) and scalloping of the enamel at the DEJ, suggesting osteoclastic activity (Seow, 1998;Singer & others, 1991). Johnson and Harkness (1997) performed a histological study of a pre-eruptive intracoronal resorption lesion found in a pre-molar extracted for orthodontic therapy.…”
Section: Discussionmentioning
confidence: 99%